Left paraduodenal hernia causing acute bowel obstruction: report of a case and review of literature - Bhuyan, Kanakeswar; Hemanth, G. N. (International Surgery Journal, 2016)
Internal hernia is a protrusion of viscera or a part of it through a normal or abnormal peritoneum or mesenteric aperture and into a compartment of the abdominal cavity. This condition is difficult to diagnose preoperatively because of its non-specific presentation. It may remain silent or present as severe acute intestinal obstruction. Paraduodenal hernias are common type of internal abdominal hernia accounting to 53% and the majority of it (75%) is of left sided. Imaging study especially contrast-enhanced computed tomography abdomen during a symptomatic episode can make a diagnosis preoperatively. We report a case of 24 year male with left paraduodenal hernia presenting with acute intestinal obstruction.